Sejarah Kampung Adat Tuaninu di Kusa Belu Nusa Tenggara Timur - Maria Odelia Bria; Andreas Ande; Silvanus Jefrino Mali (Jurnal Global Ilmiah, 2026)
The objectives of this research are to explore the History of the Tuaninu Traditional Village in Kusa Belu, East Nusa Tenggara; the Meaning and Value of Each Element within the Tuaninu Traditional Village in Kusa Belu, East Nusa Tenggara; and the Current Condition of the Tuaninu Traditional Village in Kusa Belu, East Nusa Tenggara. Informants were selected using purposive sampling technique. The data sources used in this research include primary and secondary data sources. Data collection techniques involved observation, interviews, and document studies. Data analysis technique: historical analysis. The research results indicate that: The history of Tuaninu, as recorded in oral tradition, is a narrative of mobility, political strategy, and identity formation within the power networks of Wehali-Wewiku and the sandalwood trade economy. This traditional village is a living cultural landscape, where each element such as settlement patterns, banyan trees, fortresses, bahane (ritual objects), traditional houses, and heirloom objects serves as active symbols and learning media that reproduce the community's value system and cosmology. The close interrelation among these elements creates a sacred space that preserves the transmission of religious, social, moral, and historical values across generations. Physically and ritually, the village still maintains traditional architecture, prohibits modern buildings in the core area, and preserves heirloom objects. The main challenge is the decreasing number of young generations residing in the village. However, strong belief in ancestors and customary rules forms the foundation of cultural resilience, making Tuaninu a living space that continuously integrates spirituality, identity, and local knowledge in a holistic manner.